Evaluasi dan Perbaikan User Experience Menggunakan User Experience Questionnaire (UEQ) dan Heuristic Evaluation (HE) Pada Produk Gift Card Tiket.com - Faisal Risq Efendy; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Gift Card products was one of product developed by Tiket.com that works for helping user to buy Gift Card from Tiket.com. This product has not been evaluated for user experience to the user, so the level of difficulity has not been known yet. In this research an evaluation was conducted with User Experience Questionnaire (UEQ) to know the level of Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, also Novelty from the users and evaluation was conducted with Heuristic Evaluation (HE) to dig deeper the main problem from the evaluator. The result of evaluation for the overall old design got a Good score, with a benchmark score for every point of assessment got a Good score for Atrractiveness, Efficiency, Dependability, Stimulation and Novelty point, while Perspicuity point got an Above Average score. From the old design has found 23 problems with detail 9 problems was found by respondent, and 21 problems was found by evaluator, 7 problems which found by respondent also found by the evaluator. From the evaluation process for design repair solutions overall got Excellent result with detail for every point got Excellent score for Attractiveness, Efficiency, Dependability, Stimulation, and Novelty point while Perspicuity got Good score.